Low-Dose Valganciclovir for CMV Prophylaxis after Lung Transplantation. (4th December 2012) - Khurana, Hargobind S.; Kole, Alison; Falk, Jeremy; Ghandehari, Sara; Soohoo, Guy; Simsir, Sinan; Cheng, Wen; Kass, Robert M.; Khurana, Jasjit; Chaux, George
Abstract : Purpose . Cytomegalovirus (CMV) remains an important pathogen following solid organ transplantation (SOT). Universal prophylaxis for CMV is adopted by most centers after lung transplantation. Various combinations studied for CMV prophylaxis include intravenous and oral ganciclovirs, oral valganciclovir, and CMV immunoglobulins. We present our experience with a low-dose of oral valganciclovir for CMV prophylaxis following lung transplantation. Methods and Materials . Our center started using 450 mg of daily oral valganciclovir for CMV prophylaxis in lung transplant recipients in Jan, 2001. A retrospective chart analysis of patients who underwent lung transplantation from January 2001 to December 2006 was done. Of 46 patients, 4 were excluded as they died within 30 days of transplant from postop complications. The mean age at transplant was 64 years, mostly single lung transplants (36/6) with a male-to-female ratio of 25/17. COPD was the most common reason for transplant (65%), and the serological CMV status of donors (D) and recipients (R) was as follows: D+/R+ 28, D+/R− 5, D−/R+ 5, and D−/R− 4. Valganciclovir was given for a total of 6 months posttransplant except for D−/R+ patients who received it for 12 months. Results . Five patients (12%) developed CMV disease with an average followup of 26 months. Only 2 (4.7%) developed CMV disease within six months of completing valganciclovir prophylaxis. This incidence is not significantly different from the best-reported results of CMV prophylaxis in lung transplant recipients. The remaining 3 patients developed the disease later in their course, one as late as 32 months posttransplant. The main side effects noted include leucopenia, neutropenia, and GI disturbances. However, the number of patients who had to temporarily stop or discontinue the medication (9.5%) was significantly lower than that reported in previous studies. Conclusions . Our experience suggests that low-dose valganciclovir is an effective method of prophylaxis for CMV disease in high-risk patients. It is a simple regimen that seems to have a better side effect profile and to improve patient compliance.